2018
DOI: 10.1080/02670844.2017.1381376
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesised WC-reinforced Co-based alloy layer by vacuum cladding

Abstract: Co-based alloy cladding layers (wallex50 and wallex55) were synthesised on 316L stainless steel by vacuum cladding. Experimental results showed that wallex50 composed of γ-Co, WC, Co 6 W 6 C, Cr 7 C 3 , in which in situ reinforcement WC phases were homogeneously distributed in the layer, having a clear and stable interface structure. Wallex55 with externally added WC particles was composed of γ-Co, WC, Co 6 W 6 C, Cr 7 C 3 , CrB, CoWB. The average microhardness of wallex50 and wallex55 was 794 ± 29 and 939 ± 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…During the cladding process, reactions among Fe, B, Cr, and Ni atoms might lead to the FeNi 3 and CrB phase formation in both cases. The presence of WC peak in the WC-NiCrBSi cladding coating is owing to the externally added WC particles, while in the case of IWC-NiCrBSi coating, the presence of WC peak confirms the in-situ reaction between W and C element in the matrix during the vacuum cladding process, and the probable reactions are as follows [22]:
Figure 1 XRD pattern of (a) WC-NiCrBSi and (b) IWC-NiCrBSi cladding coating.
…”
Section: Resultsmentioning
confidence: 99%
“…During the cladding process, reactions among Fe, B, Cr, and Ni atoms might lead to the FeNi 3 and CrB phase formation in both cases. The presence of WC peak in the WC-NiCrBSi cladding coating is owing to the externally added WC particles, while in the case of IWC-NiCrBSi coating, the presence of WC peak confirms the in-situ reaction between W and C element in the matrix during the vacuum cladding process, and the probable reactions are as follows [22]:
Figure 1 XRD pattern of (a) WC-NiCrBSi and (b) IWC-NiCrBSi cladding coating.
…”
Section: Resultsmentioning
confidence: 99%
“…The carbide could be precipitated from the coating by heating the Ni-W alloy under certain parameters. WC has been synthesized in situ by laser cladding, improving the properties of Ni coating and Co alloy coating [10,11]. Su et al [12] found that the high-frequency induction heat treatment of Ni-W alloy coating yielded Ni 4 W and Ni 6 W 6 C precipitates, achieving a 1100 Hv coat hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, introducing an appropriate amount of ductile phase into the metal silicide composite through the alloying process can effectively improve its toughness. In general, the introduced phase possesses excellent low room-temperature toughness and high-temperature strength [10][11][12].…”
Section: Introductionmentioning
confidence: 99%